Pengaruh Layanan Perpustakaan terhadap Tingkat Kepuasan Mahasiswa Sekolah Pascasarjana Universitas Negeri Padang - Rahayu, Desy Setia; Rahmah, Elva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of library services on student satisfaction at the Graduate School of Universitas Negeri Padang. High-quality library services are expected to contribute significantly to student satisfaction and academic success, particularly in supporting the search and utilization of scholarly information. However, several issues were identified, such as the limited availability of up-to-date references, the absence of an independent digital repository at the graduate library, and varied student perceptions regarding service quality. This study employed a quantitative approach. The research instrument was developed based on service indicators from the LIBQUAL model and student satisfaction indicators derived from the Expectation Confirmation Theory (ECT), which includes dimensions of expectation, perceived performance, and confirmation or disconfirmation. The findings indicate that library services are categorized as very good, with an achievement rate of 82.2%, while student satisfaction falls under the good category with a rate of 75.07%. Regression analysis results show a significant influence of library services on student satisfaction, with a significance value of 0.000 and an R square of 0.569. This means that 56.9% of the variance in student satisfaction can be explained by the quality of library services. These findings highlight the need for improvements, particularly in enhancing access to digital collections and developing an independent repository system, to better meet user expectations.